A model to jointly determine inventory and credit policies in an inventory system with date-terms credit linked demand. (1st January 2013) - Aggarwal, K.K.; Tyagi, Arun Kumar
In order to increase sales over and above cash sales, firms generally give trade credit to their customers. Trade credit policy through its influence on demand becomes a determinant of inventory policy which is intended to meet that demand. Therefore, inventory and trade credit policies are interrelated which should be determined simultaneously in a systems perspective. However, inventory policy is generally determined independent of the credit policy. This paper develops a mathematical model for simultaneously determining inventory and credit policies when demand rate consists of: 1 cash demand rate 2 credit demand rate depending upon date-terms credit period. Discounted cash flow approach has been used to establish the model. The objective of the model is to maximise the present value of firm' s net profit per unit time by jointly determining the optimal date-terms credit period and replenishment time. Numerical example and sensitivity analysis are presented to illustrate the effectiveness of proposed model and results are discussed. The model suggests that at high values of inventory carrying cost and accounts receivable carrying cost the firm should invest less in accounts receivables by following a tight credit policy.